2009
DOI: 10.4028/www.scientific.net/msf.624.71
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Sintering of SiC-Ceramics

Abstract: The most interesting feature in silicon carbide is the structure-property relation where the formation of different types of microstructure due to different structural modifications (polytypism) and grain-boundary/interfacial phase chemistry dictate the final properties of the monoliths. Since synthesis of SiC in last century, several methods such as hot pressing with a sintering aid (B, C), pressureless sintering with a sintering aid (B, C, Al) and reaction bonded (Si-SiC) were used to fabricate dense SiC. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…For solid-state pressureless-sintered SiC ceramics using B 4 C and C as sintering additives, the densification process always accompanied with SiC grain coarsening. During the sintering process, smaller SiC grains, with small radii of curvature, tended to evaporate and condense on the larger particles, resulting in coarsening of the microstructure without the elimination of pores [20]. In addition, too much carbon (here means graphene) blocked the mass transport processes, and this was ineffective for densification.…”
Section: Resultsmentioning
confidence: 99%
“…For solid-state pressureless-sintered SiC ceramics using B 4 C and C as sintering additives, the densification process always accompanied with SiC grain coarsening. During the sintering process, smaller SiC grains, with small radii of curvature, tended to evaporate and condense on the larger particles, resulting in coarsening of the microstructure without the elimination of pores [20]. In addition, too much carbon (here means graphene) blocked the mass transport processes, and this was ineffective for densification.…”
Section: Resultsmentioning
confidence: 99%
“…confirmed that the outer rim area, about 200 nm thick, had the tendency to coalesce and this region was characterized indeed by tight SiC grains, coarser than in the core of the fiber and with lower content of dark phase. This behavior is quite reasonable since C removal can induce coarsening and coalescence of the SiC crystallites fiber [11,17]. The fiber morphology is displayed in TEM images in Fig.…”
Section: Fiber Evolutionmentioning
confidence: 94%
“…The fracture is mainly intergranular, owing to the presence of carbon itself acting as weak interphase. Excess of carbon is actually reported to inhibit grain growth and to maintain equiaxed microstructure [17].…”
Section: Fiber Evolutionmentioning
confidence: 99%
“…23 Although many theories have been proposed to explain the means by which sintering aids such as boron or B 4 C activate sintering, no explanation has yet been clearly established. 12,13 According to Prochazka and Scanlan, 2 the high grain boundary to surface energy ratio (γ GB /γ SV ) makes it difficult to sinter pure silicon carbide. Boron was then thought to segregate to the grain boundary reducing their energy and thus decreasing γ GB /γ SV .…”
Section: Sintering Mechanismmentioning
confidence: 99%
“…12,13 This study intends to report the pressureless sintering of nanocrystalline ␤ phase silicon carbide with addition of boron carbide and carbon. The activation energy of sintering was determined.…”
Section: Introductionmentioning
confidence: 99%